2011
DOI: 10.1517/14728214.2011.537824
|View full text |Cite
|
Sign up to set email alerts
|

Emerging drugs for uveitis

Abstract: Importance of the Field Uveitis is a challenging disease covering both infectious and noninfectious conditions. The current treatment strategies are hampered by the paucity of randomized controlled trials (RCTs) and few trials comparing efficacy of different agents. Areas Covered in this Review This review describes the current and future treatments of uveitis. A literature search was performed in PUBMED from 1965 to 2010 on drugs treating ocular inflammation with emphasis placed on more recent, larger studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 119 publications
3
60
0
11
Order By: Relevance
“…Основные группы иммуносупрессивных препаратов представлены анкилирующими агентами, антиметабо-литами, ингибиторами Т-клеток и так называемыми био-логическими модуляторами иммунного ответа (biologic response modifiers или BRMs) [27,28,29].…”
Section: современные тенденции в лечении увеитовunclassified
See 2 more Smart Citations
“…Основные группы иммуносупрессивных препаратов представлены анкилирующими агентами, антиметабо-литами, ингибиторами Т-клеток и так называемыми био-логическими модуляторами иммунного ответа (biologic response modifiers или BRMs) [27,28,29].…”
Section: современные тенденции в лечении увеитовunclassified
“…К группе ингибиторов Т-клеток относят кальцинев-риновые ингибиторы циклоспорин и такролимус, ко-торые нарушают дифференцировку и пролиферацию Т-клеток [27,28,30].…”
Section: современные тенденции в лечении увеитовunclassified
See 1 more Smart Citation
“…Examples of steroid antiinflammatory include prednisone and fluocinolone (Callanan et al 2008; The Multicenter Uveitis Steroid Treatment Trial Research et al 2011), and immunosuppressive agents include methotrexate, mycophenolate, azathioprine, and cyclosporine. In some cases, immune-specific biological response modifiers such as rituximab, abatacept, daclizumab, and the TNF-α inhibitors, infliximab and adalimumab, are also used (Larson et al 2011;Nussenblatt et al 1999;). Prednisone, a mixture of glucocorticoid and mineralocorticoid, would likely bind to both intracellular glucocorticoid (GR) and mineralocorticoid receptor (MR) complexes and control gene transcription via direct and indirect mechanisms.…”
Section: Uveitismentioning
confidence: 99%
“…While methotrexate is most commonly administered orally, it can also be given via subcutaneous or intravitreal injections. When given orally, up to 35% of the dose is metabolized by intestinal flora prior to absorption; however, when parenterally administered, it is fully absorbed (Gangaputra et al 2009;Larson et al 2011). Gangaputra and colleagues retrospectively reviewed the records of 384 patients identified from the Systemic Immunosuppressive Therapy for Eye Diseases (SITE) Study and found no significant difference in the effectiveness of subcutaneous versus oral routes of administration (Gangaputra et al 2009).…”
Section: Methotrexatementioning
confidence: 99%